Odpowiedzi

2009-11-19T22:03:01+01:00
A) (3x-1)(4x+5)=(4x+5)(2x-1) /:(4x+5)
3x-1=2x-1
3x-2x=-1+1
x=0
b)51-y(3y+4)=2(17-2y)-58
51-3y² -4y= 34-4y-116
-3y² -4y+4y +51-34+116=0
-3y²+133=0
Δ=1596
√Δ=2 √399
y₁=-2√399 / -6 =1/3* √399 lub y₂=2√399/-6= -1/3√399

c) (2+5x)²=19x + (x-4)(x+5)
4+20x+25x²=19x + x² +5x -4x -20
25x²-x² +20x-19x-5x+4x +4+20=0
24x² +24 =0
Δ=-2304
wyróżnik jest ujemny czyli brak rozwiązania
2009-11-19T22:03:25+01:00
A) (3x-1)(4x+5)=(4x+5)(2x-1) /:(4x+5)
3x-1=2x-1
3x-2x=0
x=0

b)51-y(3y+4)=2(17-2y)-58
51-3y²-4y=34-4y-58
-3y²=34-58-51
-3y²=-75 /:(-3)
y²=25
y=√25 =5

c)(2+5x)²=19x+(x-4)(x+5)
4+20x+25x²=19x+x²+5x-4x-20
20x+25x²-19x-x²-5x+4x=-20-4
24x²=-24 / :(24)
x²=-1
x=-1²